Does Mandibular Distraction Osteogenesis for Robin Sequence Create Altered Craniofacial Morphology and Disrupt Tooth Development? - Greenlee, Geoffrey M.; Willett, Emily; Susarla, Srinivas; Evans, Kelly N.; Mancl, Lloyd; Sheller, Barbara (Journal of oral and maxillofacial surgery, 2024)
Robin Sequence (RS) infant patients may require mandibular distraction osteogenesis (MDO) to improve airway. The distracted mandible may grow vertically and the developing dentition may be disrupted. The study purpose was to measure the association of MDO on craniofacial morphology and tooth development in RS subjects. This was a retrospective cohort study of RS infants treated with or without MDO. Inclusion criteria were RS diagnosis, complete imaging, and treatment at our pediatric regional hospital. Exclusion criteria were treatment elsewhere and insufficient imaging. Exposure was airway management; subjects were grouped by use of MDO or not. Subjects were compared to age-matched normal infants presurgically and to age-matched normal controls at follow-up. Main outcome variables were craniofacial morphology measured using cephalometric gonial angle and ramus height to mandibular body length ratio presurgically (T1), postsurgically (T2), and at the mixed dentition (T3). Disrupted tooth development was assessed by absence/abnormality of teeth on radiographs at T3. Covariates were age, sex, body mass index, comorbidities, and cephalometric measurements. Appropriate univariate, bivariate, and regression models were computed, and significance level was set at P < .05. The sample contained 14 RS-MDO subjects with median age of 1.1 months and 10 (71.4%) were female. Presurgery, RS-MDO subjects had significantly more obtuse gonial angles (145° vs 137°, P = .04) and shorter mandibular bodies (32 vs 41 mm, P < .01) than the 37 unaffected controls. Increased ramus height (P < .01) and mandibular body length (P < .01) and forward rotation of the mandible were seen in 12 subjects with post-MDO imaging compared to their presurgical condition. At mixed dentition, 12 post-MDO subjects had more obtuse gonial angles (P < .01) and steeper mandibular planes (P < .01) than 19 non-MDO RS subjects. Both RS groups had different cephalometric values and more vertical measures than matched cephalometric norms. Thirty-one percent of 12 RS-MDO subjects had ≥1 teeth with abnormal development compared to none of 19 RS subjects without MDO (P = .02). MDO increased mandibular size in infants but can disrupt the developing dentition. Postdistraction growth may result in more vertical mandibular morphology with large gonial angles.